Enriba da terra: da sinergia individual para a coletiva refletindo a partir do Quilombo de Cana Brava - Paixão, Raimundo Mauricio Matos (2015)
The current Master‘s dissertation has a two-pronged approach. Firstly, a self reflection regarding my own journey was made, going from a person who used to consider itself as a dark one, and which was hit by my racist practices of Brazilian society, until the path that led me to Black Culture Center (BCC) what, as a result, made me become black and unveiled my collective face, as a part of black struggles in Brazil. This discovery leads us to the second approach: the involvement with quilombo comunities – what made me upgrade and spread about the knowledges, the practices and great experiences. Thus, I work this last theme through a case study with the Quilombo Community Cana Brava, located in Santa Quiteria city, State of Maranhão (Brazil). I seek to understand how the forms of political organization of the community and its ways of creating, making and living express this strength in so many other quilombo communities in Brazil.